Single-photon Source Based on Self-Assembled Quantum Dots and Its Applications - Wang, Wenjing (Transactions on Computer Science and Intelligent Systems Research, 2024)
Over the past few decades, extensive exploration has been conducted on quantum dot light sources. Researchers have continuously improved the synthesis techniques of quantum dots, developing various materials and structures to enhance their optical performance and stability. This has also led to the expansion of application fields for quantum dot light sources. This paper provides a concise overview of the fundamental background knowledge on self-assembled quantum dot (QD) single-photon sources. Additionally, it explores the techniques for evaluating the standards of single-photon sources through two-photon suppression and the second-order correlation function. It reviews common self-assembled quantum dot growth methods, focusing on molecular beam epitaxy (MBE) technology and the introduction of Distributed Bragg Reflectors (DBR). Finally, this article introduces the research history of enhancing single-photon performance by modifying the quantum dot system structure. The primary measure involves enhancing single-photon emission using microcavity structures. By leveraging the tight coupling between the photons radiated by atoms, quantum dots, and other structures with the microcavity field modes, significant improvements in single-photon characteristics are achieved. Researchers have already obtained single-photon emission streams with well-regulated time intervals and time-controllable quantum dot single-photon sources. Additionally, they have been able to fabricate high-quality quantum dot light sources that exhibit high efficiency, indistinguishability, and single-photon purity.